Dielectric properties of Y-doped Ba1–xSrxTiO3 ceramics - Xu, Jing; Liu, HanXing; He, Bo; Hao, Hua; Li, YiQiu; Cao, MingHe; Yu, ZhiYong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Y-doped Ba1–xSrxTiO3 (Y-BST) ceramics (x = 0.1, 0.2, 0.4, 0.7) were prepared by solid-state reaction and sintered at 1250, 1300, 1350, and 1400 °C for 1 h. The effect of strontium solution and sintering temperature on the structure, microstructure and dielectric properties of Y-BST was investigated. SEM investigations revealed a grain size decreasing with the Sr content increase. The temperature dependence of permittivity showed decrease in phase transition temperature with higher Sr content. Enhancing sintering temperature is effective to increase the grain size and improve the microstructure porosity. The XRD patterns of all Y-doped Ba0.3Sr0.7TiO3 ceramics indicated that the crystal cell parameters increase when temperature increased. However, the (002) and (200) peaks of Y-doped Ba0.3Sr0.7TiO3 split when sintering temperature was increased to 1400 °C, which makes the structure of the specimen transit to tetragonal (a = 3.9857 Å and c = 4.018 Å) from cubic. It may be attributed to the fact that Y3+ ion can occupy both A site and B site of Ba0.3Sr0.7TiO3 sintered at 1400 °C, which leads to the large different internal stress in individual grains, and then induces the structure change. The temperature coefficient of capacitance (TCC) value of the Y-doped Ba0.3Sr0.7TiO3 sintered at 1400 °C changed little within ±6% over a temperature range from 10 to130 °C.
Optica Applicata, Vol. 40, 2010, nr 1, s. 255-264
Keywords: optyka; Y-doped; Ba1–xSrxTiO3 ceramics; dielectric properties